Spectrum of Coronary Artery Involvement With Multisystem Inflammatory Syndrome in Children Versus Kawasaki Disease - Simon Lee; Ashraf S. Harahsheh; Geetha Raghuveer; Michael A. Portman; Arash A. Sabati; Michael Khoury; Nagib Dahdah; Marianna Fabi; Supriya S. Jain; Audrey Dionne; Kyle Runeckles; Frederic Dallaire; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background There is significant overlap in clinical features between multisystem inflammatory syndrome in children (MIS‐C) and Kawasaki disease (KD). We sought to compare the prevalence, severity, and associated factors for coronary artery (CA) involvement. Methods and Results From January 1, 2020 through January 31, 2023, 1191 patients with MIS‐C and 554 patients contemporaneously diagnosed with KD were enrolled into the International Kawasaki Disease Registry. Demographic and clinical features, laboratory values, maximum Z score in any CA branch at any time point, and worst left ventricular ejection fraction, were compared between groups. Factors associated with CA aneurysms (maximum Z score in any CA branch +2.5 or greater) were determined separately for each diagnosis using multivariable logistic regression analyses. The prevalence of CA aneurysms was lower for MIS‐C versus KD (16% versus 25%, respectively; P<0.001) and less severe by size category (1.2% with medium/large CA aneurysm versus 9.6%, respectively). Male sex and lower nadir hemoglobin levels were associated with greater odds of CA aneurysms for both groups. Additional associated factors for KD patients included age<6 months, fewer clinical KD criteria (more incomplete presentation), presentation with shock, and greater total days of fever. There were no additional associated factors for patients with MIS‐C. Using exploratory splines, there was a trend of improvement in Z scores within 30 days of illness for both MIS‐C and KD for CA involvement other than large aneurysms. Conclusions CA involvement for patients with MIS‐C was less prevalent and milder in severity compared with contemporaneous patients with KD, with fewer associated factors, and a high prevalence of regression to a normal luminal dimension.